Mutation of orthologous prickle genes causes a similar epilepsy syndrome in flies and humans. Issue 9 (3rd August 2016) - Ehaideb, Salleh N.; Wignall, Elizabeth A.; Kasuya, Junko; Evans, William H.; Iyengar, Atulya; Koerselman, Haley L.; Lilienthal, Anthony J.; Bassuk, Alexander G.; Kitamoto, Toshihiro; Manak, J. Robert
Abstract: Objective: Genetically tractable fruit flies have been used for decades to study seizure disorders. However, there is a paucity of data specifically correlating fly and human seizure phenotypes. We have previously shown that mutation of orthologous PRICKLE genes from flies to humans produce seizures. This study aimed to determine whether the prickle ‐mediated seizure phenotypes in flies closely parallel the epilepsy syndrome found in PRICKLE patients. Methods: Virtually all fly seizure studies have relied upon characterizing seizures that are evoked. We have developed two novel approaches to more precisely characterize seizure‐related phenotypes in their native state in prickle mutant flies. First, we used high‐resolution videography to document spontaneous, unprovoked seizure events. Second, we developed a locomotion coordination assay to assess whether the prickle mutant flies were ataxic. Third, we treated the mutant flies with levetiracetam to determine whether the behavioral phenotypes could be suppressed by a common antiepileptic drug. Results: We find that the prickle mutant flies exhibit myoclonic‐like spontaneous seizure events and are severely ataxic. Both these phenotypes are found in human patients with PRICKLE mutations, and can be suppressed by levetiracetam, providing evidence that the phenotypes are due to neurological dysfunction. These results document for the first time spontaneous, unprovoked seizure events at high resolution in a fly human seizure disorder model, capturing seizures in their native state. Interpretation: Collectively, these data underscore the striking similarities between the fly and human PRICKLE ‐mediated epilepsy syndromes, and provide a genetically tractable model for dissecting the underlying causes of the human syndromic phenotypes.